Pengaruh Media Scrapbook terhadap Pengendalian Perilaku Prokrastinasi Akademik Siswa - Warosatun Ni'mah; Isnawati Nur Afifah Latif (Paedagogie, 2026)
This study aims to identify the level of students’ academic procrastination, analyze the effect of using scrapbook learning media on controlling such behavior, and measure the magnitude of its effect in Islamic Cultural History (SKI) learning. The study employed a quantitative approach using a quasi-experimental method with a Non-Equivalent Control Group Design. The research was conducted at MAN 1 Tuban with a sample of 62 students, consisting of 30 students in the experimental group and 32 students in the control group. Data were collected using a Likert-scale questionnaire administered through pretest and posttest stages. Data analysis was conducted using a paired sample t-test. The results showed that the mean pretest score of 60.07 increased to 64.00 in the posttest. The significance value of 0.039 was lower than 0.05, indicating that the use of scrapbook learning media had a significant effect on controlling students’ academic procrastination behavior. An effect size of 0.39 indicated a small-to-moderate effect. Therefore, scrapbook learning media can be considered sufficiently effective in helping reduce students’ academic procrastination behavior while making the Islamic Cultural History (SKI) learning process more engaging, structured, and meaningful for students.